2019
DOI: 10.3390/w11102020
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Holding Time for Agricultural Water Testing EPA Method 1603 for Produce Growers

Abstract: Agricultural water is a known vector for the transfer of foodborne pathogens onto fresh produce. Development of pre-harvest and post-harvest microbial profiles of agricultural water used by fresh produce growers, processors, and holdings is a requirement under the Food Safety Modernization Act Produce Safety Rule. One of the United States Environmental Protection Agency (US EPA) approved agricultural water testing methods is US EPA Method 1603, which requires no greater than a 6-h time frame between the collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Under such conditions, previous authors have found no significant difference between E. coli counts after 6 h and after 24 h (Bhullar et al . 2019 ). When we compared water samples from control and UV‐treated plots that were shipped on the day of sampling compared to the following day, we observed no statistically significance in the logodds of a sample being positive for RifR E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…Under such conditions, previous authors have found no significant difference between E. coli counts after 6 h and after 24 h (Bhullar et al . 2019 ). When we compared water samples from control and UV‐treated plots that were shipped on the day of sampling compared to the following day, we observed no statistically significance in the logodds of a sample being positive for RifR E. coli .…”
Section: Discussionmentioning
confidence: 99%